Study on the factors associated with postpartum visits in rural China - You, Hua; Dong, Hengjin (PLOS ONE, 2013)
Background Postpartum visits (PPVs) have been advocated as a way to improve health outcomes for mothers and their infants, but the rate of PPVs is still low in rural China. This study aims to investigate the utilization of PPVs and to explore the factors associated with PPVs in rural China. Parity is the most concerned factor in this study. Methods A cross-sectional household survey was performed in two counties of Zhejiang province. Questions include socio-economic, health services and women's delivery data. Chi-square tests and multivariate logistic regression analyses were performed to identify factors associated with PPVs. Results 223 women who had a delivery history in the recent five years were enrolled in analyses. 173 (78%) of them were primiparous. Among the primiparous women, 43 (25%) had not received any PPVs. The majority, 27 (55%) of the 49 multiparous women, had not received any PPVs. Multiparous women were less likely to receive PPVs than primiparous women. Among 223 puerperal women, 47 (21%) had been compensated for delivery fee expenses. Women who received compensation were found to be more likely to receive standard (at least 3) PPVs. Conclusions It was found that women with “second babies” were less likely to use PPVs. This could be an unintended consequence of the “one-child policy”, due to fear that contact with public health facilities could result in sanctions. This phenomenon should be taken seriously by government in order to improve the health of babies and their mothers. Financial compensation for delivery fee charges can improve the use of PPVs, thus free-of-charge delivery should be promoted.
Gesehen am 26.07.2021